Identification and evaluation of clinical factors in high-risk pregnancies - Almeida, Pedro Augusto Marcondes de; Ciari Junior, Cyro; Siqueira, Arnaldo Augusto Franco de; Schor, Néia; Giron, Sueli Gandolfi; Tanaka, Ana Cristina d'Andretta (Revista de Saúde Pública, 1975)
The identification of high-risk pregnancies is very important, because it allows correct protection of pregnancy and puerperium. In order to simplify this procedure, a risk chart containing four groups of clinical factors which might determine or aggravate high-risk pregnancies, is presented.